Histomorphologic spectrum of ovarian cystic lesions at a tertiary care centre - Dr. Anand Kanasagara; Dr. Ankur Sarvaiya; Dr. Dhaval Sakariya (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: An ovarian cyst is a liquid or semi-liquid material filled sac in an ovary. Proper management depends on the histomorphological division of nonneoplastic & benign and malignant neoplastic lesions. So this study was done to differentiate the lesion histomorphologically and to know the commonest lesion in each age group. Objectives: To study age wise incidence, nonneoplastic, benign and malignant spectrum of ovarian cystic lesions. Methods: A retrospective histo-pathological study of 100 cases of nonneoplastic and neoplastic cystic lesions of ovary was conducted. Result: We found that out of 100 cases, 58% were non neoplastic and 42% were neoplastic. Benign cystic teratoma was the most common neoplastic condition. Follicular cyst was the commonest nonneoplastic condition. Conclusion: Histomorphological parameters along with advanced newer diagnostic modalities like immunohistochemistry can help to do early diagnosis and plan the line of treatment & they have effect on prognostic significance.